The Tokyo War Crimes Trial : The Pursuit of Justice in the Wake of World War II - Totani, Yuma, 1972- (Book collections on Project MUSE., 2009)
Yuma Totani assesses the historical significance of the International Military Tribunal for the Far East (IMTFE) - commonly called the Tokyo trial - established as the eastern counterpart of the Nuremberg trial in the immediate aftermath of World War II.